The Role of Innovation Type and Startup Performance in Mediating the Influence of Entrepreneurial Intention on Business Sustainability - Rizcho Louistama Setyana Putra; Kussudyarsana Kussudyarsana; Moechammad Nasir (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to determine whether innovation type and startup performance mediate the influence of entrepreneurial intention on business sustainability. This study is Explanatory Research with a Quantitative approach. The sample size of this study was 187 respondents. Using the SmartPLS software. Partial Least Square (PLS) was used to analyze the data in this study. The results of this study are Entrepreneurial Intention has a significant effect on Business Sustainability. Entrepreneurial Intention has a positive and significant effect on Innovation Type. Entrepreneurial Intention has a positive and significant effect on Startup Performance. Innovation Type has a positive and significant effect on Startup Performance. Innovation Type has a positive and significant effect on Business Sustainability. Startup Performance has a positive and significant effect on Business Sustainability. Innovation Type and Startup Performance can mediate the influence of Entrepreneurial Intention on Business Sustainability.